2022
DOI: 10.3390/cancers14133165
|View full text |Cite
|
Sign up to set email alerts
|

WNT/β-Catenin-Mediated Resistance to Glucose Deprivation in Glioblastoma Stem-like Cells

Abstract: Isocitrate dehydrogenase (IDH)-wildtype glioblastoma is the most common primary malignant brain tumor. It is associated with a particularly poor prognosis, as reflected by an overall median survival of only 15 months in patients who undergo a supramarginal surgical reduction of the tumor mass followed by combined chemoradiotherapy. The highly malignant nature of IDH-wildtype glioblastoma is thought to be driven by glioblastoma stem-like cells (GSCs) that harbor the ability of self-renewal, survival, and adapta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Given the growing evidences that m6A is associated with Wnt signaling 5 , 6 , while recognizing that Wnt/β-catenin plays an inevitable role in GBM 7 9 , there may be possible mechanisms for their yet to be elucidated interplay in the pathogenesis of GBM. Concerning the functional regulation of m6A, the fine-tuning and interactions between the m6A and long non-coding RNAs (lncRNA) axis have been considered.…”
Section: Introductionmentioning
confidence: 99%
“…Given the growing evidences that m6A is associated with Wnt signaling 5 , 6 , while recognizing that Wnt/β-catenin plays an inevitable role in GBM 7 9 , there may be possible mechanisms for their yet to be elucidated interplay in the pathogenesis of GBM. Concerning the functional regulation of m6A, the fine-tuning and interactions between the m6A and long non-coding RNAs (lncRNA) axis have been considered.…”
Section: Introductionmentioning
confidence: 99%
“…33 AXIN2, a negative inhibitor of the Wnt signalling pathway, regulates the phosphorylation and degradation of β-catenin, thus promoting the overexpression of target genes, affecting cell proliferation and differentiation, and promoting the occurrence of tumours. [34][35][36] In this study, we showed that tRF…”
Section: Discussionmentioning
confidence: 57%
“… 33 AXIN2, a negative inhibitor of the Wnt signalling pathway, regulates the phosphorylation and degradation of β‐catenin, thus promoting the overexpression of target genes, affecting cell proliferation and differentiation, and promoting the occurrence of tumours. 34 , 35 , 36 In this study, we showed that tRF‐19‐PNR8YPJZ bound to AXIN2 and that overexpression of this receptor activated the Wnt/β‐catenin pathway by decreasing AXIN2 expression. Knockdown of tRF‐19‐PNR8YPJZ prior to PSC‐derived exosome treatment reversed its effects on Wnt/β‐catenin pathway activation.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“… 30 The elevated expression of HIF1α can activate multiple intracellular signaling pathways, such as the Wnt/β-catenin axis, to maintain the stemness of GSCs, promote the expression and clonal proliferation of GSCs, and finally induce GSCs to differentiation into surrounding progeny tumor cells, further promoting tumor angiogenesis and enhancing invasion ability of tumor. 31 , 32 SENP1 can maintain HIF1 α stability, and activation of multiple signaling pathways under hypoxic conditions, promoting tumor growth and invasiveness. 33 Based on the phenomenon that the malignant behaviors of GSCs under hypoxia depended on deSUMOylation revealed by our experimental results, it is reasonable to deduce that SENP1-mediated deSUMOylation can serve as an important target for regulating the malignant behaviors of GSCs, which implied that downregulation of SENP1 not only inhibited the proliferation, migration, and differentiation abilities of GSC but also prevented tumor tissue remodeling.…”
Section: Discussionmentioning
confidence: 99%